Cardiac Ion Channelopathies and the Sudden Infant Death Syndrome - Wilders, Ronald (International Scholarly Research Network, 2012)
The sudden infant death syndrome (SIDS) causes the sudden death of an apparently healthy infant, which remains unexplained despite a thorough investigation, including the performance of a complete autopsy. The triple risk model for the pathogenesis of SIDS points to the coincidence of a vulnerable infant, a critical developmental period, and an exogenous stressor. Primary electrical diseases of the heart, which may cause lethal arrhythmias as a result of dysfunctioning cardiac ion channels (“cardiac ion channelopathies”) and are not detectable during a standard postmortem examination, may create the vulnerable infant and thus contribute to SIDS. Evidence comes from clinical correlations between the long QT syndrome and SIDS as well as genetic analyses in cohorts of SIDS victims (“molecular autopsy”), which have revealed a large number of mutations in ion channel-related genes linked to inheritable arrhythmogenic syndromes, in particular the long QT syndrome, the short QT syndrome, the Brugada syndrome, and catecholaminergic polymorphic ventricular tachycardia. Combining data from population-based cohort studies, it can be concluded that at least one out of five SIDS victims carries a mutation in a cardiac ion channel-related gene and that the majority of these mutations are of a known malignant phenotype.